School Performance - Lamas, Héctor A. (2015)
The school performance study of students is, due to its relevance and complexity, one of the issues of major controversy in the educational research, and it has been given special attention in the last decades. This study is intended to show a conceptual approach to the school performance construct, contextualizing the reality in the regular basic education classrooms. The construct of learning approaches is presented as one of the factors that influences the school performance of students. Besides, an outlook of the empirical research works related to variables that are presented as relevant when explaining the reason for a specific performance in students is shown. Finally, some models and techniques allowing an appropriate study of school performance are presented.